Pengembangan Bahan Ajar Apresiasi Puisi Berbasis Pendidikan Karakter dalam Syair Nasib Melayu Karya Tenas Effendy: Pengembangan Bahan Ajar yang Berorientasi Pada Pendidikan Karakter: Buku Syair Nasib Melayu Karya Tenas Effendy dalam Mata Kuliah Apresiasi Puisi - Rahayu, Sri; Ningsih, Rika; Andika, Zaldi; Sukmawati, Rina (GERAM: Gerakan Aktif Menulis, 2023)
This research is motivated by the importance of increasing character education for students. The decline in character or morals in students is of great concern to the world of education. There are lots of deviant or immoral behaviors being carried out by students today including the use of illegal drugs/narcotics, free sex and many other deviant behaviors that can put a black mark on the world of education. Improving character education can be done through the development of poetry appreciation teaching materials on aspects of the poetic genre in the form of poetry. The purpose of this research is to find out whether teaching materials for poetry appreciation, especially poetry, are oriented towards improving character education for students. The research approach used in this research is a qualitative approach with a research method that is descriptive analytic. As a qualitative research, it is descriptive in nature as data analysis and the results of the analysis are in the form of phenomena from all the wealth of information about the implementation of learning poetry appreciation. The level of success will be measured by the assessment matrix from the results of tests and interviews. Character values ​​are taken from eighteen values ​​from the results of the Ministry of National Education's study.